2013
DOI: 10.1177/0884533612467824
|View full text |Cite
|
Sign up to set email alerts
|

Drug–Vitamin D Interactions

Abstract: Extensive media coverage of the potential health benefits of vitamin D supplementation has translated into substantial increases in supplement sales over recent years. Yet, the potential for drug-vitamin D interactions is rarely considered. This systematic review of the literature was conducted to evaluate the extent to which drugs affect vitamin D status or supplementation alters drug effectiveness or toxicity in humans. Electronic databases were used to identify eligible peer-reviewed studies published throu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
48
0
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(52 citation statements)
references
References 148 publications
(161 reference statements)
0
48
0
4
Order By: Relevance
“…Several drugs may potentially impact the metabolism of vitamin D. Any drug that interferes with vitamin D absorption, metabolism and/or excretion process could potentially alter the action of vitamin D [35]. Several drugs are known to impact one of the two hydroxylation steps of vitamin D: (1) the hydroxylation of vitamin D to 25-hydroxyvitamin D (25(OH)D) via cytochrome P450 vitamin D 25-hydroxylase (25-OHase or CYP27A1) or (2) the hydroxylation of 25(OH)D to 1,25-dihydroxyvitamin D (1, 25(OH) 2 D) via the cytochrome P450 D-1-α-hydroxylase (1-OHase or CYP27B1) [36].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several drugs may potentially impact the metabolism of vitamin D. Any drug that interferes with vitamin D absorption, metabolism and/or excretion process could potentially alter the action of vitamin D [35]. Several drugs are known to impact one of the two hydroxylation steps of vitamin D: (1) the hydroxylation of vitamin D to 25-hydroxyvitamin D (25(OH)D) via cytochrome P450 vitamin D 25-hydroxylase (25-OHase or CYP27A1) or (2) the hydroxylation of 25(OH)D to 1,25-dihydroxyvitamin D (1, 25(OH) 2 D) via the cytochrome P450 D-1-α-hydroxylase (1-OHase or CYP27B1) [36].…”
Section: Discussionmentioning
confidence: 99%
“…In a classic endocrine feedback loop, high blood concentrations of vitamin D also induces its own catabolism by increasing the expression of the 25-hydroxyvitamin D-24-hydroxylase (CYP24A1) which plays an important role in the catabolism of vitamin D [37]. Anti-convulsive medications such as phenytoin and phenobarbital can increase CYP24A1 expression, which results in the lowering of serum vitamin D [35].…”
Section: Discussionmentioning
confidence: 99%
“…Vitamin D status in adults with epilepsy is less clear. Several studies have failed to find that patients on EIAEDs have lower vitamin D levels than those on non-enzyme-inducing AEDs (Non-AEDs) (Vestergaard, 2005; Pack et al, 2005; Pack et al, 2011a), and a recent systematic review found insufficient evidence to determine if AEDs alter serum 25-hydroxyvitamin D levels (Robien et al, 2013). The prevalence of vitamin D deficiency in adults with epilepsy and its relationship to specific AEDs remain uncertain.…”
Section: Introductionmentioning
confidence: 99%
“…Notably, vitamin D deficiency is highly prevalent and severe during the immediate post-transplant period following solid organ transplantation (e.g., heart, liver or kidney transplantation) and persists in long-term allograft recipients [87][88][89][90][91][92][93][94]. This may be due to several factors, namely: (i) inadequate vitamin D dietary intake or supplementation after transplantation [91,95]; (ii) reduced sun exposure (usually recommended to organ transplant recipients in order to prevent the risk of skin cancer related to long-term immunosuppression) [96,97]; and (iii) increased vitamin D catabolism or reduced vitamin D hydroxylation induced by glucocorticoids and/or immunosuppressive drugs [87,[98][99][100][101]. Therefore, vitamin D deficiency should be promptly diagnosed and treated in organ transplant recipients, since it can potentially result in secondary hyperparathyroidism and bone loss [102,103], which can be further exacerbated by the detrimental skeletal effects mediated by immunosuppressive drugs [104].…”
Section: Role Of Vitamin D In Clinical Solid Organ Transplantationmentioning
confidence: 99%